Relationship Between Lower-limb Strength and Y-balance Test in Elderly Women - Eun-hye Kim; Sung-hoon Jung; Hwa-ik Yoo; Yun-jeong Baek; Oh-yun Kwon (Korean Research Society of Physical Therapy, 2023)
Background: Falls are a common and serious problem in the elderly population. Muscle strength and balance are important factors in the prevention of falls. The Y-balance test (YBT) is used to assess dynamic postural control and shows excellent test-retest reliability. However, no studies have examined the relationship between lower-limb strength and YBT scores in elderly women. Objects: This study aimed to examine the relationship between lower-limb strength and YBT scores in elderly women. Methods: Thirty community-dwelling elderly women participated in the study. Lower-limb strength including hip flexor, hip extensor, hip abductor (HAB), hip adductor (HAD), knee flexor, knee extensor, ankle dorsiflexor, and ankle plantar flexor (PF) muscles was examined using a smart KEMA strength sensor (KOREATECH Inc.), and the YBT was used to assess dynamic balance. Relationship between lower-limb strength and YBT was demonstrated using a Pearson's correlation coefficient. Results: HAB strength (r = 0.388, p < 0.05), HAD strength (r = 0.362, p < 0.05), and ankle PF strength (r = 0.391, p < 0.05) positively correlated with the YBT-anterior direction distance. Ankle PF strength was positively correlated with the YBT-posteromedial direction distance (r = 0.396, p < 0.05) and composite score (r = 0.376, p < 0.05). Conclusion: The results of this study suggest that HAB, HAD, and ankle PF strengths should be considered for dynamic postural control in elderly women.